Impact of Core Stability Training and Valsalva Maneuver on Balance and Specific Skills: A Comprehensive Study in College Soccer Players Within the Domain of Sports and Exercise Medicine - Wenzheng Chen; Syed Kamaruzaman Bin Syed Ali; Hutkemri Zulnaidi (Revista de Psicología del Deporte (Journal of Sport Psychology), 2023)
This study emphasises the importance of understanding the central role of the core in functions such as force transfer, spinal stability, injury prevention, and precise movement control. The importance of developing core muscles to maintain good posture, improve proprioception, and enhance body composition for overall well-being is emphasised. This study rigorously evaluates the effects of core stability training and Valsalva Maneuvers (VM) on the balance and specific skills of college football players. A random sample of around 90 soccer players from a polytechnic in Sichuan Province, China, was chosen. All participants had at least two years of experience playing soccer and were between the ages of 18 and 20 on average. Two interventions were randomly assigned to two groups, while a third group served as the control. To allocate subjects, the study used an equated group design and a random group design to assign treatments. The data was analysed using ANCOVA and mean variance methods, which showed significant differences between the initial and final means of the treatment groups compared to the control group.The results indicate a positive association between core stability training, Valsalva Maneuvers, and improved balance and specific skills in athletes. Individuals who engage in these training modalities demonstrate enhancements in balance, resilience, decision-making, stamina, concentration, and tolerance. The results of this study are consistent with previous research, highlighting the importance of core stability training and Valsalva Maneuvers in enhancing athletic performance.